Isolated mildly elevated Alkaline Phosphatase (ALP) - a liver tumor hint not to be missed at primary care - Shalihin, Mohd Shaiful Ehsan; Mukhali, Hassan Basri; Nik Anuar, Nik MohdNurhafizi; Mohd, Zailani; Anuar, N Aiman (2018)
As primary care providers, it is part of our routine job scope to review laboratory result of patient come for medical screening or chronic disease follow up. It is quite common to receive a medical report of mildly deranged liver enzymes that most of us tend to treat conservatively in low risk and asymptomatic patients. The dilemma is how mildly elevated is considered mild and safe. Indeed, a further assessment is still required. We report a case of a focal nodular hyperplasia in a 31-year-old gentleman who is clinically asymptomatic, with isolated mildly elevated alkaline phosphatase (ALP). He benefited an ultrasound liver which showed dilated common bile duct. Subsequent CT scan favors diagnosis of fibrolamellar carcinoma and he was managed well with surgical intervention. We would like to report a case of liver tumor detected at a primary care clinic based on an incidental finding of mildly elevated ALP.